The Role of Quality 4.0 in Business Process Management: a Bibliometric Study - Korir, Gerald; Benedek, Petra (International Journal of Engineering and Management Sciences, 2025)
Quality 4.0 builds on the principles of Industry 4.0 to improve quality management. Integrating Quality 4.0 into Business Process Management (BPM) examines how digital technologies enhance process efficiency and innovation. The main research question is how Quality 4.0 can be aligned with existing BPM frameworks and how the digital transformation of traditional quality management techniques facilitates efficiency. A bibliometric analysis was conducted using the Scopus database, employing keyword analysis, link mining techniques, and network mapping to identify research trends and gaps. The results show the main directions of research on integrating Quality 4.0 and BPM and highlight implementation barriers such as organizational resistance and the need for strategic alignment. The study also suggests directions for future investigation, including the development of standardized frameworks for evaluating digital BPM outcomes and exploring emerging debates around human-centric, sustainable, and resilient approaches reflected in Industry 5.0 and Quality 5.0.